Integrated miRNAome and Transcriptome Analysis Reveals Argonaute 2-Mediated Defense Responses Against the Devastating Phytopathogen Sclerotinia sclerotiorum - Jia-Yi Cao (Frontiers in Plant Science, 2020)
Argonaute 2 (AGO2)-mediated role in plant defense against fungal pathogens remains largely unknown. In this study, integrated miRNAome and transcriptome analysis employing ago2 mutant was performed to reveal AGO2-associated miRNAs and defense responses against the devastating necrotrophic phytopathogen Sclerotinia sclerotiorum. Both miRNAome and transcriptomes of S. sclerotiorum-inoculated ago2-1 mutant (ago2-Ss) and wild-type (WT-Ss) as well as mock-inoculated ago2-1 mutant (ago2) and wild-type (WT) Arabidopsis plants, were analyzed by sRNA and mRNA deep sequencing. Differentially expressed genes (DEGs) and differentially expressed miRNAs (DEMs) of the comparisons WT-Ss/WT, ago2/WT, ago2-Ss/WT-Ss, and ago2-Ss/ago2 were identified. Furthermore, integration analysis for the DEMs and DEGs identified over 40 potential AGO2-dependent Sclerotinia sclerotiorum-responsive (ATSR) DEM-DEG pairs involving modulation of immune recognition, calcium flux, redox homeostasis, hormone accumulation and signaling, cell wall modification and metal ion homeostasis. Data-mining result indicated that most of the DEMs were bound with AGO2. Moreover, Arabidopsis mutant analysis demonstrated that three ROS and redox homeostatasis related DEGs of identified DEM-DEG pairs, GSTU2, GSTU5, and RBOHF contributed to the AGO2-mediated defense against S. sclerotiorum. This work provides genome-wide prediction of miRNA–target gene pairs that are potentially associated with the AGO2-dependent resistance against S. sclerotiorum.